Identification of quantitative trait loci associated with calmness and gentleness in honey bees using whole‐genome sequences. (10th May 2021) - Guichard, M.; Dainat, B.; Eynard, S.; Vignal, A.; Servin, B.; ,; Neuditschko, M.
Summary: The identification of quantitative trait loci (QTL) through genome‐wide association studies (GWAS) is a powerful method for unravelling the genetic background of selected traits and improving early‐stage predictions. In honey bees ( Apis mellifera ), past genetic analyses have particularly focused on individual queens and workers. In this study, we used pooled whole‐genome sequences to ascertain the genetic variation of the entire colony. In total, we sampled 216 Apis mellifera mellifera and 28 Apis mellifera carnica colonies. Different experts subjectively assessed the gentleness and calmness of the colonies using a standardised protocol. Conducting a GWAS for calmness on 211 purebred A. m . mellifera colonies, we identified three QTL, on chromosomes 8, 6, and 12. The two first QTL correspond to LOC409692 gene, coding for a disintegrin and metalloproteinase domain‐containing protein 10, and to Abscam gene, coding for a Dscam family member Abscam protein, respectively. The last gene has been reported to be involved in the domestication of A . mellifera . The third QTL is located 13 kb upstream of LOC102655631, coding for a trehalose transporter. For gentleness, two QTL were identified on chromosomes 4 and 3. They are located within gene LOC413669, coding for a lap4 protein, and gene LOC413416, coding for a bicaudal C homolog 1‐B protein, respectively. The identified positional candidate genes of both traits mainly affect the olfaction and nervous system of honey bees. Further research is needed to confirm the results and to better understand the genetic and phenotypic basis of calmness and gentleness.